The Improvement of Students’ Problem-Solving Skills Through 5E Learning Model - Haris Rosdianto; Chat Teeka (Jurnal Pendidikan Indonesia, 2019)
This research aimed to describe the effect of the 5E learning model on students’ problem-solving skills in the topic of static fluid. The type of this research is pre-experimental study with One Group Pretest-Posttest Design. The population in this research were all eighth grade students of SMP Torsina Singkawang. The sampling technique used in this study was purposive sampling with a total sample of 23 students. Because it is not normally distributed, the data were analyzed using non-parametric statistical tests, which is Mc Nemar Test. From the calculation was obtained the value of χ2obtained > χ2critical or 15.059 > 3.841, then H0 was rejected amd Ha accepted at the level of significance α = 0.05. So it can be concluded that the 5E learning model has a positive effect on students’ problem-solving skills in the topic of static fluid.